The Fourth Industrial Revolution: Another Industrial Revolution Leaving Black Women Behind? - Malaika Mahlatsi (The Thinker)
In 2016, Klaus Schwab – founder and Executive Chairman of the World Economic Forum (WEF) – introduced a term that would have significant consequences for global politics, economics, science, and the way in which the world is organised. The Fourth Industrial Revolution (4IR), according to Schwab’s book by the same title, would be different in scale, scope and complexity from any that the world had seen before. This fusion of advances in complex technologies, including but not limited to robotics, quantum computing, blockchain, artificial intelligence (AI) and the internet of things (IoT), would affect all disciplines and industries of the modern world. It would reconstruct space, economies, governments and even challenge existing ideas about what it means to be human (Schwab, 2016).